Prevalence of coronary artery calcification in patients with end-stage renal disease undergoing dialysis and the association of various risk factors with the development of coronary artery calcification in this patient population - Avisek Maity (Asian Journal of Medical Sciences, 2024)
Background: Patients with end-stage renal disease (ESRD) on dialysis exhibit a significantly higher risk of coronary artery calcification (CAC) than age-matched normal individuals, contributing to elevated cardiovascular morbidity and mortality. Aims and Objectives: This study designed to assess the prevalence of CAC in ESRD patients on dialysis and identify associated risk factors. Materials and Methods: Fifty ESRD patients undergoing maintenance dialysis and twenty normal subjects were included in this cross-sectional observational study. Serum calcium, phosphate, and parathyroid hormone were measured in all ESRD patients and normal controls. Multi Row Spiral Computed Tomography was performed to determine CAC scoring (CACS). Results: CACS was significantly higher in ESRD patients compared to normal subjects (mean CACS: 91.4±32.7 vs. 7.75±9.5 Agatston units, P<0.05). Elevated levels of calcium phosphate products, serum leptin, intact parathyroid hormone (iPTH), presence of diabetes mellitus, and longer duration of dialysis were correlated with increased incidence of CACS in ESRD patients, as indicated by higher odd’s ratios ranged from 1.10 to 6.93. Conclusion: CAC is highly prevalent in ESRD patients on dialysis, emphasizing the need for stringent risk factor management. Our findings suggest that controlling calcium phosphate product, serum leptin, age, iPTH levels, and duration of dialysis may reduce CAC burden in this population, potentially mitigating cardiovascular risk and improving outcomes.